Nutrition education workshop for narcotics users: an experience report (Research, Society and Development, 2020)
Chemical dependence is a generic term for psychological and / or physical dependence on an exogenous substance. Being free from hunger and eating healthy and adequate food are fundamental human rights. Drug addicts due to social vulnerability and health risks that affect their nutritional status to some extent encouraged the project through workshops and meetings held from November 2014 to February 2015 at a long-term facility for drug addicts. The objective of the study was to describe the experiences and the nutritional education workshops held during this period. The results were positive where it was possible to notice changes in eating habits and behaviors in addition to improving well-being and success in treatment. From this it is suggested that new projects be carried out with this type of audience, as activities such as this modify and improve the self-esteem and well-being that is a support for the successful treatment of chemical dependence.